2022
DOI: 10.1002/ptr.7700
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as a therapeutical option for the treatment of thrombotic complications associated with COVID‐19

Abstract: The SARS‐CoV‐2 outbreak has been one of the largest public health crises globally, while thrombotic complications have emerged as an important factor contributing to mortality. Therefore, compounds that regulate the processes involved in thrombosis could represent a dietary strategy to prevent thrombotic complications involved in COVID‐19. In August 2022, various databases were consulted using the keywords “flavonoids”, “antiplatelet”, “anticoagulant”, “fibrinolytic”, and “nitric oxide”. Studies conducted betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…By constructing and analyzing databases and network diagrams of traditional Chinese medicine prescriptions, we identified quercetin, beta-sitosterol, and kaempferol as highly correlated with DVT. Previous studies demonstrated that quercetin and its derivatives possess anticoagulant, antiplatelet, and antifibrinolytic activities [ 37 , 38 ], effectively preventing pulmonary thromboembolism [ 39 ]. Furthermore, onion extracts rich in quercetin regulate MAPK under coagulation stimulation to prolong thrombosis time [ 40 ], consistent with our KEGG enrichment analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…By constructing and analyzing databases and network diagrams of traditional Chinese medicine prescriptions, we identified quercetin, beta-sitosterol, and kaempferol as highly correlated with DVT. Previous studies demonstrated that quercetin and its derivatives possess anticoagulant, antiplatelet, and antifibrinolytic activities [ 37 , 38 ], effectively preventing pulmonary thromboembolism [ 39 ]. Furthermore, onion extracts rich in quercetin regulate MAPK under coagulation stimulation to prolong thrombosis time [ 40 ], consistent with our KEGG enrichment analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that quercetin and its derivatives possess antifibrinolytic, anticoagulant, and antiplatelet properties. [ 35 , 36 ] Moreover, in mouse models, quercetin has been shown to inhibit thrombosis by inhibiting protein disulfide isomerase (PDI). [ 37 ] Both kaempferol and quercetin are flavonoids that regulate the interaction between fibrinogen and thrombin to prevent thrombosis while inhibiting prothrombin activity in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…They can inhibit the aggregation of platelets, the blood cells responsible for forming clots. This inhibition reduces the risk of blood clot formation, which can lead to stroke, heart attack, and other cardiovascular complications [ 98 ]. While more research is needed to fully elucidate the mechanisms underlying these benefits, accumulating evidence suggests that flavonoids play a protective role in various aspects of human health.…”
Section: Flavonoidsmentioning
confidence: 99%